Combining health insurance funds in a fragmented context: what kind of challenges should be considered? - Mohammad Bazyar; Arash Rashidian; Minoo Alipouri Sakha; Mohammad Reza Vaez Mahdavi; Leila Doshmangir (BMC, 2020)
Abstract Background Iran's Parliament passed a Law in 2010 to merge the existing health insurance schemes to boost risk pooling. Merging can be challenging as there are differences among health insurance schemes in various aspects. This qualitative prospective policy analysis aims to reveal key challenges and implementation barriers of the policy as introduced in Iran. Methods A qualitative study of key informants and documentary review was conducted. Sixty-seven semi-structured face-to-face interviews were conducted, with key informants from relevant stakeholders. Purposive and snowball sampling techniques were used for selecting the interviewees. The related policy documents were also reviewed and analyzed to supplement interviews. Data analysis was conducted through an existing health financing World Bank framework. Results This study demonstrated that for combining health insurance funds, operational challenges in the following areas should be taken into account: financing mechanisms, population coverage, benefits package, provider engagement, organizational structure, health service delivery and operational processes. It is also important to have adequate cogent reasons to "the justification of the consolidation process" in the given context. When moving towards combining health insurance funds, especially in countries with a purchaser-provider split, it is critical for policy makers to make sure that the health insurance system is aligned with the policies and Stewardship of the broader health care system. Conclusions Implementation of major reforms in a health system with fragmented insurance schemes with different target populations, prepayment structures, benefit packages and history of development is inherently difficult, especially when different stakeholders have vetoing powers over the proposed reforms. Solving the differences and operational challenges in the main areas of health insurance system generated in this study may provide a platform for the designing and implementing merging process of social health insurance schemes in Iran and other countries with similar situations.